Boundary value problems for fractional differential inclusions with Hadamard type derivatives in Banach spaces - GRAEF, John R.; GUERRAICHE, Nassim; HAMANI, Samira (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
The authors establish sufficient conditions for the existence of solutions to boundary value problems for fractional differential inclusions involving the Hadamard type fractional derivative of order α ∈ (1, 2] in Banach spaces. Their approach uses M¨onch’s fixed point theorem and the Kuratowski measure of noncompacteness. Mathematics Subject Classification (2010): 26A33, 34A08, 34A60, 34B15.